1997
DOI: 10.1103/physrevb.56.r1708
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-doped dimer rows on Si(001)

Abstract: The stability and electronic structure of a nanowire are studied by first-principles calculations. The wire consists of a single depassivated silicon dimer row on the hydrogen passivated Si͑001͒ 2ϫ1 surface. We predict that sodium atoms evaporated onto this surface stick preferentially at the depassivated row and partially fill the empty one-dimensional states of this row. This leads to a thin metallic wire of atomic size dimensions. At room temperature the sodium atoms are mobile along the depassivated row; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…4,35 Gallium 12,13 and silver 4 atoms diffuse fast on the hydrogenated surface but stick to DBs. Arsenic, 36 gold, 11 and sodium 37 atoms might follow the same path.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,35 Gallium 12,13 and silver 4 atoms diffuse fast on the hydrogenated surface but stick to DBs. Arsenic, 36 gold, 11 and sodium 37 atoms might follow the same path.…”
mentioning
confidence: 99%
“…In addition to templating molecules, silicon DB rows also hold promise to form self-assembled wires of selected atoms. , Gallium , and silver atoms diffuse fast on the hydrogenated surface but stick to DBs. Arsenic, gold, and sodium atoms might follow the same path.…”
mentioning
confidence: 99%
“…Second, the conductivity of the metal wire depends critically on the deposition sites of the metal atoms as well as the species of the metal atoms. [33][34][35] It is, therefore, not clear whether the "atom wires" actually conduct, even with the atomically precise fabrication.…”
Section: Nanolithographymentioning
confidence: 99%
“…Haye et al 5 investigated Na-doped dangling bond wires fabricated on the H-terminated Si͑100͒ surface. They found that for low coverages, Na atoms act simply as electron donors, and that the shapes of the surface energy bands resemble those of a clean Si͑100͒ surface, except for the position of the Fermi level.…”
mentioning
confidence: 99%
“…Therefore, we tried to dope an electron into this band by adding one K atom to the unit cell of geometry ͑a͒. 14 Here, we chose an alkali atom as a dopant because Haye et al 5 showed that an alkali atom acts as an ideal electron donor for an atomic wire on the H-terminated Si͑100͒ surface. We tried three starting geometries of K adsorbates, all considered stable.…”
mentioning
confidence: 99%